Leadership traits as the basis for effective interaction between the leader and the team - Nataliia Aliekperova; Adyl Aliekperov (Journal of Leadership in Organizations, 2023)
Introduction/Main Objectives: The study proposed is written based on the results of quantitative research and the analysis of the theory and practice of leadership. The study's main objective is to determine the essential traits of a leader for effective interaction with team members. Background Problems: Most research on this topic chose a leader's traits based on analyzing literary sources rather than on empirical research. Novelty: The traits for the most effective collaboration between leader and team members were chosen by potential and actual members of the leader's team, namely students and teachers of the University. Research Methods: We conducted a questionnaire survey of 103 teachers and 421 Bogomolets National Medical University (Kyiv) students. The statistical analysis was carried out using Wald Test. Finding/Results: The research confirmed that both respondent categories admitted the importance of all leadership traits. At the same time, such traits as passion, effectiveness, self-confidence, determination, and ability to take risks appeared to be more significant for the students than for the teachers. The teachers ranked such a trait as decency higher than the students did. Also, such issues as the importance of organizational culture, ethical aspects of leadership, and the most effective leadership style for productive interaction with team members were examined. Conclusion:  This study proposed complex recommendations for creating the most productive model of the interaction between the leader and team members based on the data obtained.